0.6*(2у-11)=0.4(у-7)-7.48
0.6(2y-11)=0.4y-2.8-7.48
0.6(2y-11)=0.4y-10.28
1.2y-6.6=0.4y-10.28
(1.2y-0.4y)-6.6=-10.28
0.8y-6.6=-10.28
0.8y=6.6-10.28
0.8y=-3.68
------------------------------------
0.2*(0.6у-33)=0.2*(2у-0.6)-10.16
0.2*(0.6у-33)=0.4y-0.12-10.16
0.2(0.6y-33)=0.4y-10.28
0.12y-6.6=0.4y-10.28
(0.12y-0.4y)-6.6=-10.28
-0.28y-6.6=-10.28
-0.28y=6.6-10.28
-0.28y=-3.68
0.6*(2у-11)=0.4(у-7)-7.48
0.6(2y-11)=0.4y-2.8-7.48
0.6(2y-11)=0.4y-10.28
1.2y-6.6=0.4y-10.28
(1.2y-0.4y)-6.6=-10.28
0.8y-6.6=-10.28
0.8y=6.6-10.28
0.8y=-3.68
------------------------------------
0.2*(0.6у-33)=0.2*(2у-0.6)-10.16
0.2*(0.6у-33)=0.4y-0.12-10.16
0.2(0.6y-33)=0.4y-10.28
0.12y-6.6=0.4y-10.28
(0.12y-0.4y)-6.6=-10.28
-0.28y-6.6=-10.28
-0.28y=6.6-10.28
-0.28y=-3.68